MgBr2-mediated ionic Diels-Alder reaction of acetals of alpha,beta-unsaturated aldehydes and ketones with 1,3-dienes - Chavan, Subhash P.; Ethiraj, Krishna S.; Dantale, Shubhada W. (Synthetic Communications, 2007)
A facile, mild, and efficient methodology for the ionic Diels-Alder reaction of acetals of alpha,beta-unsaturated ketones and aldehydes as dienophiles with various 1,3- dienes employing MgBr2 as the Lewis acid catalyst to furnish corresponding Diels-Alder adducts at ambient temperature is described.
Keywords: acetals; Catalysts; Diels-Alder reactions; dienes